Intrauterine growth retardation in Iowa communities with herbicide-contaminated drinking water supplies. - Munger, R (1997)
In a statewide survey of 856 Iowa municipal drinking water supplies in 1986-1987 the Rathbun rural water system was found to contain elevated levels of triazine herbicides. Rates of low birth weight, prematurity, and intrauterine growth retardation (IUGR) in live singleton births during the period 1984-1990 by women living in 13 communities served by the Rathbun water system were compared to other communities of similar size in the same Iowa counties. The Rathbun communities had a greater risk of IUGR than southern Iowa communities with other surface sources of drinking water (relative risk = 1.8; 95% CI = 1.3, 2.7). Multiple linear regression analyses revealed that levels of the herbicides atrazine, metolachlor, and cyanzinc were each significant predictors of community IUGR rates in southern Iowa after controlling for several potentially confounding factors including maternal smoking and socioeconomic variables. The association with IUGR was strongest for atrazine, but all three herbicides were intercorrelated and the independent contributions of each to IUGR risk could not be determined. We conclude that communities in southern Iowa with drinking water supplies contaminated with herbicides have elevated rates of IUGR compared to neighboring communities with different water supplies. Because of the limitations of the ecologic design of this study, including aggregate rather than individual measures of exposure and limited ability to control for confounding factors related to source of drinking water and risk of IUGR, a strong causal relationship between any specific water contaminant and risk of IUGR cannot yet be inferred. The association between the water supplied to the Rathbun communities and the increased risk of IUGR should be considered a preliminary finding that needs to be verified by more detailed epidemiologic studies.